The Relationship Of Motivation With The Learning Outcames Of Basic Subjects Culinary Basics - Gusnira, Febrianur; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research started from researchers' observations of students of SMK Negeri 3 Solok City, where not a few of them always arrived late and even often missed coming to school, thus affecting their scores and getting low learning outcomes. This study aims to: (1) describe students' learning motivation in basic culinary subjects at SMK Negeri 3 Solok City. (2) describe student learning outcomes in basic culinary subjects at SMK Negeri 3 Solok City. (3) analyze the relationship of student learning motivation in basic culinary subjects. This research uses quantitative descriptive method with a correlational approach. The population of this study was class X Tata Boga students at SMK Negeri 3 Solok City for the 2022/2023 academic year and the research sample was 40 people using simple random sampling. Data were collected using a research instrument in the form of a learning motivation questionnaire consisting of 39 positive statements and 13 negative statements and student learning outcomes data using first semester report card scores. The results showed that (1) Student learning motivation in Basic – Basic Culinary subjects as a whole was in interval classes in the moderate category with a total of 14 respondents (35 %), while (2) Learning outcomes of Basic subjects – Basic Culinary based on first semester report card scores are in interval classes in the high category with a total of 20 people (50%) of students getting low scores. Only 2 people (5%) students get high scores. (3) Furthermore, the normality analysis test of the data obtained is normally distributed with a value of 0.853 > 0.05, while the linearity analysis of the data obtained is linear distributed with a value of 0.819 > 0.05. The correlation test showed that 0.489 of the medium category corresponds to the interpretation value of r. The significance value is known to be 0.001 < 0.05, which means that there is a significant positive relationship between the learning motivation variable and learning outcomes. The results of the t test showed that the known calculated t value of 3,458 thus t count > t table (3,458 > 1,684) statistically then Ho was rejected and Ha was accepted, meaning that the first hypothesis in the study was accepted.. Keyword: Motivation, Learning Outcomes, Culinary Basics